THE EFFECT OF AB MIX NUTRIENT CONCENTRATION AND LIQUID ORGANIC FERTILIZER ON GROWTH AND YIELD OF PAKCOY (Brassica rapa L.) IN HYDROPONIC WICK SYSTEM - Wahyuningsih, Munirotul; Triani, Nova; Tarigan, Puji Lestari (Yayasan Education and Social Center, 2024)
Pakcoy is a vegetable that is useful and popular with Indonesian people today. The demand for pak choy is increasing, but the problem of land conversion is causing productive land to decline. Hydroponics is one solution for cultivating pak choy. The growth and development of pak choy requires AB Mix and NASA POC nutrition. This research aims to determine the effect of AB Mix and NASA POC concentrations and to determine the interaction between the two. This research is a factorial experimental study with two factors arranged using a Completely Randomized Design. The first factor is the AB Mix concentration with three levels: 600 ppm, 900 ppm, and 1,200 ppm. Meanwhile, the second factor is NASA POC concentration with five levels: 0 ml/L, 3 ml/L, 5 ml/L, 7 ml/L, and 9 ml/L. The results of the study showed that there was an interaction between AB Mix concentration and NASA POC concentration, which had a significant effect on the parameters of plant height aged 30 HSPT, number of leaves, wet weight of the crown, and wet weight of the roots